2019
DOI: 10.36457/gizindo.v42i2.459
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Orang-Tua Dalam Meningkatkan Kepatuhan Siswi Minum Tablet Zat Besi Folat Di Kota-Depok

Abstract: One strategy to reduce anemia in adolescent girl age was through school-based iron folic-acid supplementation. Parents have the important role in improving the female students' compliance. This study aim to identify parent's knowledge, attitude and their role to improve female student's compliance to consume iron folic-acid tablets, mechanism and supplementation period and female student's compliance. Using a cross sectional design, 135 parents had involved for 3 months from 9 high-schools in Depok area.The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
1
0
7
Order By: Relevance
“…These results can be seen from the good control card in the intervention group of senior high school, it was found that iron supplement consumption was reached at 100%. The results of this study have similarities with research conducted on female students in Depok City, showing that the role of parents was closely related to adherence to taking iron folate tablets for female students (Apriningsih et al, 2019). The results of this study were strengthened by the results of research conducted on Middle School students in Bogor City which showed that the teacher's role was a determining factor in female students' drinking iron supplements adherence (Nuradhiani et al, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…These results can be seen from the good control card in the intervention group of senior high school, it was found that iron supplement consumption was reached at 100%. The results of this study have similarities with research conducted on female students in Depok City, showing that the role of parents was closely related to adherence to taking iron folate tablets for female students (Apriningsih et al, 2019). The results of this study were strengthened by the results of research conducted on Middle School students in Bogor City which showed that the teacher's role was a determining factor in female students' drinking iron supplements adherence (Nuradhiani et al, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…A study conducted by Risva et al (2016) among first-year students at the Faculty of Public Health, Universitas Diponegoro, Semarang reported that attitudes, culture and environmental support had a significant relationship with iron tablet consumption. In line with this, a study conducted byApriningsih et al (2019) reported that parents played an important role in the adherence of adolescents in consuming iron tablets. In this preliminary study, 73% of respondents had Hb levels of 12 g/dl.…”
mentioning
confidence: 55%
“…Adapun perbandingan jumlah penderita anak-anak pada kelompok umur tertentu yaitu 5-14 tahun sebanyak 26,8% sedangkan 15-24 tahun sebanyak 32% [6]. Seperti yang telah diketahui bersama bahwa untuk menamatkan permasalahan anemia pada remaja putri ini pemerintah Indonesia memprogramkan pemberian tablet tambah darah di lingkungan sekolah dan fasilitas pelayanan kesehatan pemerintah [7]. Banyaknya tablet tambah darah yang diterima oleh remaja putri di sekolah adalah 52 butir yang diberikan 1 butir dalam setiap minggunya selama 1 tahun [6].…”
Section: Pendahuluanunclassified